Cooperative sensing method considering malicious nodes in cognitive radio networks - Xiao-gang QI; Sheng-yu ZHENG; Li-fang LIU; Hui-fang WANG (Tongxin xuebao)
Based on a more practical cognitive radio network with malicious users,the spectrum sharing network model based on the cooperative spectrum sensing was studied that the secondary user can dynamically adjust its transmit power based on cooperative sensing results.To avoid significant reduction in performance of spectrum sensing system caused by malicious nodes,it is aimed to study how to improve the performance of cooperative sensing.By introducing the convex optimization problem,the secondary network throughput is maximized under the certain detection probability conditions and the corresponding power constraints.Simulation results show that whether or not there are malicious nodes,the algorithm is efficient in calculating optimal sensing time and the optimal transmit powers,and the secondary network throughput is increased when the maximum interference power limits and the maximum transmit power restrictions are decreased.